1994
DOI: 10.1177/074355489492005
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Perceptions and Interethnic Strategies among French, Italian, and Haitian Adolescents of a Multiethnic School in Montreal

Abstract: Processes through which interethnic relations and identity are constructed in a natural situation were studied among French, Italian, and Haitian adolescents of a multiethnic high school in Montreal. Grounded theory was the methodology chosen to study how the microsocial and macrosocial contexts influence the development of attitudes and strategies of individuals and groups. The research was conducted mainly through interviews of groups offriends (n = 4 to 6) of the same ethnic origin, gender, and age. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Social networks and friendships are assumed to be associated with cultural (ethnic and national) identity and social interaction may provide an avenue by which ethnicity is experienced and explored (Laperrière, Compère, D’Khissy, Dolce, & Fleurant, 1994). Phinney, Romero, Nava, and Huang (2001) have observed that interaction with peers from one's own ethnic group predicts ethnic identity, while parental cultural maintenance has only an indirect effect through adolescent ethnic language proficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Social networks and friendships are assumed to be associated with cultural (ethnic and national) identity and social interaction may provide an avenue by which ethnicity is experienced and explored (Laperrière, Compère, D’Khissy, Dolce, & Fleurant, 1994). Phinney, Romero, Nava, and Huang (2001) have observed that interaction with peers from one's own ethnic group predicts ethnic identity, while parental cultural maintenance has only an indirect effect through adolescent ethnic language proficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In the same multi-ethnic schools, class differences mitigate citizen efficacy, for although young people share the same general view of society across social classes, lower-class youth feel more constricted and less enabled to participate in broader societal discourses and activities than middle-class youth (Laperri6re & Dumont,in press). Yet again, gender and social class in the same schools also played differential roles in each ethnic group in determining attitudes and strategies toward diversity (Laperri6re, Comp6re, D'Khissy, Dolce, & Fleurant, 1994). The 12-13-year-olds share Revue de I'integratiou et de la migration internationale 237 tt f2BERT, SHIRLEY SUN, and KOWCH a dominant taboo on the topic of diversity, whereas the 14-15-year-olds celebrate it, and among the 16-17-year-olds sharp divisions are reported between subgroups that are open or closed to ethnic differences in the fifth year of high school.…”
Section: The Influence Of Schoolsmentioning
confidence: 96%